Wujud Alih Kode dan Campur Kode Dalam Lirik Lagu Letting Go - Handayani, Siti (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2023)
The phenomenon of code switching and code mixing has become commonplace in everyday life. Code switching is a situation where someone uses different language changes in communicating. Meanwhile, code mixing is a situation where someone mixes two or more languages ​​in communicating. The purpose of this study is to describe the form of code switching and code mixing contained in the song Letting Go. The method used is qualitative by collecting data and the results are presented descriptively. This study uses a sociolinguistic study approach. The results of the research show that there is a form of code switching and code mixing in the song. The form of code switching contained in the lyrics of the song Letting Go is in the form of intersentential switching. This form of code switching occurs between clauses or sentence boundaries, where language switching occurs at sentence boundaries in different languages, namely from Mandarin to English or vice versa. Then, the form of code mixing contained in this study is in the form of inserting elements in the form of repetition of words.